(untitled) (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Exogenous factors such as topography of the region are often overlooked in determining the pattern of economic activity. In fact, the geographical surface contributes to the spatial distribution of varied economic activities. The purpose of this study was to see the linkage between the efficiency of the disbursement of People’s Business Credit (KUR) program and the topography of the region in Pati Regency-Central Java. The research method is descriptive qualitative by overlaying the efficiency level of 35 KUR channeling banks with polygon maps of each subdistrict in Pati regency. Data on the efficiency level of unit banks are secondary data of each bank unit which has been calculated with Data Envelopment Analysis (DEA) application. Is it dicovered that unit banks are very inefficient at topographies bordered with arid limestone mountains or along rivers that often overflows. As a result, economic activity is not optimal and the disbursement of KUR is not efficient at the area. On the contrary, at topographies in the lowlands, the trade, agriculture, and fisheries sectors are advanced, population is large, economic activities are fast, thus encourage efficient credit disbursement.